INFORMATION SYSTEM DESIGN COMPLETENESS OF FILLING OUT DISCHARGE SUMMARY OF INPATIENTS - Fransiska Ayu Veren Nyoman Sebastianus; Edi Suharto (Jurnal Teknik Informatika (Jutif), 2022)
The discharge summary or also known as a medical resume is a sheet that contains a detailed explanation or summary of important information about the patient, this sheet is part of the medical record.The summary of discharge of patients who are hospitalized is one of the criteria used to assess the quality of hospital health care because the summary of discharge is a very important record, in which there is information about the patient's diagnosis while the patient is hospitalized. There are also medical and non-medical interventions that have been carried out by health workers to patients. The discharge summary must be filled out correctly and completely. There were problems found in hospital x, such as there was still a discharge summary that had not been filled out completely so it had to be returned to the patient's room, also the process of checking the completeness of the discharge summary and making reports were still done manually, which was typed in Microsoft excel. The purpose of this research is to create a specific information system for process of analyzing the completeness of filling in inpatient discharge summary. The method applied is qualitative research methods and descriptive and data collection techniques with direct observation at hospital x and interviews with medical record officers on duty, and the development of the system used is SDLC with the waterfall method through the stages of analysis, design, coding, and testing. The design of this program uses visual basic programming on microsoft visual studio 2010 by making reports using crystal reports. Based on the results of blackbox testing, this program gets good results. All menus in this program can run properly and exactly according to their functions.